Meeting the multiscale challenge: representing physiology processes over ApiNATOMY circuits using bond graphs. Issue 1 (6th February 2018) - de Bono, B.; Safaei, S.; Grenon, P.; Hunter, P.
Abstract : We introduce, and provide examples of, the application of the bond graph formalism to explicitly represent biophysical processes between and within modular biological compartments in ApiNATOMY. In particular, we focus on modelling scenarios from acid–base physiology to link distinct process modalities as bond graphs over an ApiNATOMY circuit of multiscale compartments. The embedding of bond graphs onto ApiNATOMY compartments provides a semantically and mathematically explicit basis for the coherent representation, integration and visualisation of multiscale physiology processes together with the compartmental topology of those biological structures that convey these processes.